(untitled) (Asian Journal of Plant Biology, 2023)
Large sections of tomato farming rely heavily on surface irrigation because rainfall is insufficient to supply crop water needs. This technique may result in water waste. Throughout and directly afterwards transplanting, at flowering, and during the development of fruit, tomatoes are extremely susceptible to water deficiencies. Therefore, preserving agricultural water supplies and boosting water productivity, coupled with increased tomato production, necessitate satisfying the water needs of tomatoes. This is why we set out to investigate how water stress affects tomato’s (Tandilo and Rukuta varieties) agro-morphological traits in this study. The research was conducted at the Botanical Garden, Gombe State University. The experiment was laid out in a Complete Randomized Block Design with six (6) replications and three (3) treatments. Three different water levels were termed as severe deficit at 14-day intervals, mild deficit at 7 d and control treatments were applied to each group. The impact of water stress on various tomato cultivars was calculated by measuring their height, stem diameter, leaf area, stem diameter, and number of branches. Water stress was found to significantly (P<0.05) reduce stem diameter, plant height, leaf area, and the number of branches. In conclusion, the agro morphological efficiency of tomato cultivars improved after modest water stress mitigation. Tandilo and Rukuta varieties can be adopted in semi-arid regions to optimize yield and ensure food security.